Relationship Between Non-Alcoholic Fatty Liver Disease and Degree of Hepatic Steatosis and Bone Mineral Density - Xie, Ruijie; Liu, Mingjiang (Frontiers in Endocrinology, 2022)
Abstract Background: The liver and bones are both active endocrine organs that carry out several metabolic functions. However, the link between non-alcoholic fatty liver disease (NAFLD) and bone mineral density (BMD) is still controversial. The goal of this study was to discover if there was a link between non-alcoholic fatty liver disease and bone mineral density in US persons aged 20 to 59 years of different genders and races. Methods: Using data from the National Health and Nutrition Examination Survey (NHANES) 2017–2018, multivariate logistic regression models were utilized to investigate the association between NAFLD and lumbar BMD. Fitted smoothing curves and generalized additive models were also used. Results: The analysis included a total of 1980 adults. After controlling for various variables, we discovered that NAFLD was negatively linked with lumbar BMD. The favorable connection of NAFLD with lumbar BMD was maintained in subgroup analyses stratified by sex, race and age in men, other race and aged 20-29 years. The relationship between NAFLD and lumbar BMD in blacks and people aged 40-49 years was a U-shaped curve with the inflection point: at 236dB/m and 262dB/m. Furthermore, we discovered that liver advanced fibrosis and liver cirrhosis were independently connected with higher BMD, while no significant differences were detected in severe liver steatosis and BMD. Conclusions: Our study found an independently unfavorable relationship between NAFLD and BMD in persons aged 20 to 59. We also discovered a positive link between BMD and advanced fibrosis and cirrhosis. More research is needed to back up the findings of this study and to look into the underlying issues.